Analyzing Amethyst Crystal Stones at the Bandung Geology Museum - Muhammad Ridwan Saputra; Rianti Rismayanti (An International Journal Tourism and Community Review, 2025)
Amethyst crystal is one type of rock that is widely studied in the field of geology, especially because of its beauty and interesting formation process. Amethyst is a variety of quartz mineral (SiO2) that is purple in color due to the presence of oxidized iron ions. As a mineral that is often used in jewelry, amethyst also has high economic value. The Geological Museum often displays amethyst crystals to provide more insight into the geological processes that occur beneath the earth's surface and the importance of recognizing various types of minerals and rocks. The purpose of exhibiting Amethyst Crystals at the Geological Museum is to provide information and knowledge to the public about the geological properties of Amethyst Crystals and their role in the world of geology and their formation process. The implications of Amethyst Crystals provide deeper insight into the geological and mineralogical processes to the public, thereby increasing understanding of the earth and nature.